Biologically active oligostilbenes from the stems of Vatica mangachapoi and chemotaxonomic significance. Issue 16 (18th August 2019) - Wu, Shou-Yuan; Fu, Yan-Hui; Zhou, Qi; Bai, Meng; Chen, Guang-Ying; Han, Chang-Ri; Song, Xiao-Ping
Abstract: Phytochemical investigation of the stems of Vatica mangachapoi (Dipterocarpaceae) led to the isolation and structural elucidation of twenty-seven oligostilbenes (1–27 ), including a new natural compound1 . The structure of1 was elucidated on the basis of spectroscopic analyses including NMR, MS and ECD data, and the known compounds were identified by comparisons with those reported in the literature. The absolute configuration of1 was first time determined by a combination of NOESY spectrum and quantum chemical computation. Among of isolates were tested for their anti-osteoporosis and anti-HIV-1 activities in vitro by the MTT method. Moreover, the chemotaxonomic significance of these compounds was summarised. Abstract :